D-dimer level as a prognostic factor in patients with acute exacerbation of chronic obstructive pulmonary disease at admission to hospital - Ahmad, Lubana Mohamad; Hejazie, Malek; Khayat, Mohamad Imad (Journal of medical and pharmaceutical sciences, 2022)
Introduction: D-dimer is a marker of thrombin and plasmin activation that has been used in the diagnostic workup of venous thromboembolism in patients with chronic obstructive pulmonary disease (COPD) admitted for acute respiratory distress. The prognostic role of elevated D-dimer levels for hospital course and in-hospital mortality in patients with AECOPD in whom deep venous thrombosis/ pulmonary embolism is excluded has rarely been evaluated. Aim: This study was designed to investigate the effect of D-dimer obtained upon admission on in-hospital mortality, the need for intensive care unit ICU admission, and the need for mechanical ventilation after acute exacerbations of chronic obstructive pulmonary disease (AECOPD). Materials and Methods: 125 participants were investigated at admission for an acute exacerbation of COPD, The age of them was between 40 and ≥70. This was an observational analytical prospective study conducted at Pulmonology Department in Tishreen University Hospital, Lattakia, Syria, during the period between June 2020 and June 2021. Clinical and laboratory data were evaluated in 108 patients (77 males,31 females) admitted for AECOPD in whom D-dimer levels were obtained upon admission and in whom (17 patients) Deep vein thrombosis/Pulmonary embolism DVT/ PE was excluded. Results: 28 (25.9%) patients needed ICU admission, 22 (20.3%) patients needed mechanical ventilation, and 19 (17.6%) patients died in the in-hospital period. D-dimer ≥ 0.5 mg/l was a risk factor for ICU admission (Relative Risk: RR 5, 95%CI: Confidence interval 1.97-12.6), for mechanical ventilation (RR 5.77, 95%CI 2.1 – 15.7), and in-hospital mortality (Relative Risk: RR 6.76, 95%CI 2.32 – 19.6). The mean age of patients with elevated D-dimer was significantly higher than patients with normal D-dimer (69.2 ± 10 VS 64 ± 12 years, P=0.037). D-dimer levels were higher in patients with renal dysfunction and congestive heart failure. A significant correlation was found between D-dimer level with hemoglobin, creatinine, and C – reactive protein (CRP). Conclusion: Elevated D-dimer is a reliable prognostic marker for short-term outcomes in patients admitted for AECOPD.